Utilizing volatile organic compounds for early detection of Fusarium circinatum - Nordström, Ida (Swedish University of Agricultural Sciences, 2022)
Fusarium circinatum, a fungal pathogen deadly to many Pinus species, can cause significant economic and ecological losses, especially if it were to become more widely established in Europe. Early detection tools with high-throughput capacity can increase our readiness to implement mitigation actions against new incursions. This study sought to develop a disease detection method based on volatile organic compound (VOC) emissions to detect F. circinatum on different Pinus species. VOCs emitted from four different Fusarium species (Fusarium circinatum, Fusarium graminearum, Fusarium bulbicola and Fusarium oxysporum f.sp. pini) grown on Elliott's media agar (in vitro), and three Pinus species (Pinus radiata, Pinus sylvestris, Pinus pinea) inoculated with either i) Fusarium circinatum or ii) mock treatment (in vivo). The four Fusarium species were grown on media and analysed in order to compare their respective VOCs profiles, while the pinus seedlings were analysed in order to determine whether Fusarium circinatum-inoculated seedlings' VOCs profiles could be distinguished from mock inoculated seedlings. The VOCs were sampled using static headspace sampling, enclosing the samples individually in (relatively inert) high-density poly-ethylene bags along with SPME fibers. Divinylbenzene/carboxen/polydimethylsiloxane SPME fibers needle size was 24 ga, 2 cm long and coated with 30 μm (CAR/PDMS layer), 50 μm (DVB layer) (Merck KGaA, Darmstadt, Germany). Immediately after sampling, the SPME fibers were manually injected through an ultra-inert, splitless, straight, 2 mm liner (Agilent, Santa Clara, USA) on a 6890N GC (Agilent Technologies, Santa Clara, USA) coupled with a 5973 MS (Agilent Technologies, Santa Clara, USA). The column was a HP-5ms ultra inert 60m GC column, 0.25 mm, 0.25 µm, 7 inch cage (Agilent, Santa Clara, USA). A C8-C20 hexane mix (Merck KGaA, Darmstadt, Germany). GC-MS was performed through MSD ChemStation version E.02.02.1431 (Agilent Technologies, Santa Clara, USA) with an initial oven temperature of 50°C, followed by an 8°C/min increase to 100°C, subsequently increasing by 4°C/min to 160°C, a final ramp of 16°C/min to 280°C and hold for 2.5 min. GC-MS data were transformed to .cdf files and processed (ADAP chromatogram builder, chromatogram deconvolution, multivariate curve resolution) and aligned (ADAP aligner) with MZMine 2 (v 2.53). Randomforest was applied to see what (if any) compounds could be useful for distinguishing between mock- or F. circinatum-inoculated seedlings (in vivo), or Fusarium species (in vitro). These compounds were tentatively identified by matching mass spectrometry data and back-calculated retention indices with literature values from authentic standards found in Nist20 and Wiley12 MS databases.

The above described pipeline applied here, entailing gas chromatography – mass spectrometry of VOCs, automated data analysis and machine learning, distinguished diseased from healthy seedlings of Pinus sylvestris and Pinus radiata. In P. radiata, this distinction was possible even before the seedlings became visibly symptomatic, suggesting the possibility for this method to identify latently infected, yet healthy looking plants. Pinus pinea, which is known to be relatively resistant to F. circinatum, remained asymptomatic and showed no changes in VOCs over 28 days. In a separate analysis of in vitro VOCs collected from different species of Fusarium, we showed that even closely related Fusarium spp. can be readily distinguished based on their VOC profiles. The results further substantiate the potential for volatilomics to be used for early disease detection and diagnostic recognition.

GC-MS data were collected both in vitro (fungal species grown on identical media) and in vivo (pine seedlings inoculated with Fusarium circinatum or mock). This GC-MS data could then be used to compare what volatile compounds were emitted from each sample and, that way, determine whether these "chemical fingerprints" of volatile compound blends differed between fungal species, or sick and healthy pine seedlings, respectively. Each data file therefore contain all the chemical compounds that can be detected by using our instruments (see general description), their mass spectas, relative abundance and retention times. No sorting of these chemical compounds have been performed, nor any other processing of this raw data for publication.

The dataset includes GC-MS data according to the Mass Spectrometry Development Kit (MSDK) data model in NetCDF format. Files can be read in software that uses MSDK, such as AMDIS or MZMine. See https://msdk.github.io/ for more possibilities.

There are 5 or 6 replicates for each time point and pine species included in the in vivo-analyses. For the in vitro analyses, there are 3 replicates per fusarium species/media blank and time point.
All in vivo files are named in the format "#DAABB*" where:
# = days post inoculation (7, 14 or 28)
D = Days
AA = Pine species (Sy=Pinus sylvestris, Ra=Pinus radiata, Pi=Pinus pinea)
BB = Inoculation type (Fc=Fusarium circinatum, Mo=Mock inoculation)
* = Replicate number (1-6)
Example: 14DPiFc4.CDF = Analysed 14 days post inoculation, Pinus pinea inoculated with F. circinatum, replicate number 4.
All in vitro files are named in the format "AAAA#*" except the media blank that is named "emabl#*" where:
AAAA = Fusarium species (fcir=Fusarium circinatum, fgra=Fusarium graminearum, foxy=Fusarium oxysporum f.sp. pini, fbul=Fusarium bulbicola)
# = days post inoculation (7, 14 eller 21)
* = replicate number (1-3)
Example: fcir72.CDF = Fusarium circinatum, Analysed 7 days post inoculation, replicate number 2

Fusarium circinatum, en svampart som orsakar dödlig sjukdom på många tallarter, kan orsaka signifikanta ekonomiska och ekologiska förluster, särskilt om den skulle bli mer etablerad i Europa. Verktyg, som möjliggör tidig detektion och provtagning av många prover samtidigt, kan öka vår beredskap och initiera förebyggande åtgärder mot nya patogener. Den här studien syftade till att utveckla ett sådant verktyg baserat på analys av flyktiga organiska ämnen (VOCs) för att kunna detektera F. circinatum på olika tallarter. VOCs som utsöndrades från fyra olika Fusariumarter (Fusarium circinatum, Fusarium graminearum, Fusarium bulbicola och Fusarium oxysporum f.sp. pini) kultiverade på Elliott's media agar (in vitro), och tre tallarter (Pinus radiata, Pinus sylvestris, Pinus pinea) inokulerade med antingen i) Fusarium circinatum eller ii) steril lösning (in vivo). De fyra Fusarium-arterna kultiverades på identiskt media och analyserades för att jämföra deras respektive VOCs-profiler, medan tallplantorna analyserades med syfte att avgöra huruvida Fusarium circinatum-inokulerade plantors VOCs-profiler kunde urskiljas från de som inokulerats med steril lösning. VOCs-prover samlades med hjälp av statisk headspace-metod, där varje enskild svampkultur/planta innesluts i en relativt inert plastpåse (high-density poly-ethylene) ihop med en SPME fiber. Divinylbenzene/carboxen/polydimethylsiloxane SPME fibrer med en nålstorlek på 24 ga, 2 cm lång och täckt med 30 μm (CAR/PDMS lager), 50 μm (DVB lager) (Merck KGaA, Darmstadt, Germany) användes för denna studie. Omedelbart efter provsamling så injicerades fibern manuellt genom en ultra-inert, splitless, straight, 2 mm liner (Agilent, Santa Clara, USA) på en 6890N GC (Agilent Technologies, Santa Clara, USA) med en 5973 MS (Agilent Technologies, Santa Clara, USA). Kolonnen var en HP-5ms ultra inert 60m GC kolonn, 0.25 mm, 0.25 µm, 7 inch cage (Agilent, Santa Clara, USA). Programvaran för GC-MS var MSD ChemStation version E.02.02.1431 (Agilent Technologies, Santa Clara, USA) med en initial ugnstemperatur på 50°C, sedan en ökning på 8°C/min till 100°C, därefter en ökning med 4°C/min till 160°C, en slutlig ökning på 16°C/min to 280°C där temperaturen hölls konstant i 2.5 min. GC-MS data exporterades till .cdf files och processerades (ADAP chromatogram builder, chromatogram deconvolution, multivariate curve resolution) och aligned (ADAP aligner) med MZMine 2 (v 2.53). Randomforest användes för att se vilka (om några) ämnen kunde användas för att särskilja F. circinatum-inokulerade tallplantor från friska (in vivo), eller särskilja de olika Fusarium-arterna (in vitro). Dessa ämnen identifierades sedan tentativt identifieras genom att matcha respektive MS data mot standarder som finns i MS-databaserna Nist20 and Wiley12.

Denna beskrivna pipeline kunde särskilja sjuka från friska tallplantor av arterna Pinus radiata och Pinus sylvestris. I Pinus radiata kunde detta göras redan innan plantan visade några symtom, vilket understryker möjligheten för detta verktyg att identifiera latent infekterade men ännu visuellt symtomfria tallplantor. Pinus pinea, som anses vara relativt resistent mot F. circinatum, förblev symtomfri och visade inga förändringar i VOCs-profil under analysperioden på 28 dagar. I en separat analys av in vitro-VOCs från fyra Fusarium-arter så kunde vi visa att även mycket nära besläktade Fusarium-arter kan särskiljas baserat enbart på deras respektive VOCs-profiler. Resultaten underbygger ytterligare potentialen för volatilomics att användas för tidig upptäckt av sjukdomar och sjukdomsdiagnostik.

GC-MS-data samlades både in vitro (svamparter odlade på identisk media) och in vivo (tallplantor inokulerade med Fusarium circinatum alt. steril lösning). Via denna GC-MS-data kunde vi jämföra vilka volatila ämnen som utsöndrades från varje enskilt prov och på så vis avgöra om dessa "kemiska fingeravtryck" av volatila ämnen skiljde sig mellan olika svamparter, respektive mellan inokulerade och friska tallplantor. Varje enskild datafil beskriver således alla kemiska föreningar som kan detekteras med hjälp av våra instrument (se allmän beskrivning), deras masspektra, relativa mängd och deras respektive retentionstid. Någon sortering av dessa kemiska föreningar har inte gjorts, ej heller någon annan bearbetning av rådatan som publiceras.

Datasetet inkluderar GC-MS data i enlighet med Mass Spectrometry Development Kit (MSDK)-datamodellen i NetCDF-format. Filer kan läsas i programvaror som använder MSDK, exempelvis AMDIS eller MZMine. Se https://msdk.github.io/ för fler möjligheter.

Det finns 5 eller 6 replikat för varje tidpunkt och tallart som ingick i in vivo-analyserna. För in vitro-analyserna finns 3 replikat per Fusarium-art/blank media och tidpunkt.
Alla in vivo-filer är namngivna enligt "#DAABB*" där:
# = dagar sedan inokulering (7, 14 eller 28)
D = Days
AA = Tallart (Sy=Pinus sylvestris, Ra=Pinus radiata, Pi=Pinus pinea)
BB = Inokuleringsagent (Fc=Fusarium circinatum, Mo=Mock, dvs steril lösning)
* = Replikatnummer (1-6)
Exempel: 14DPiFc4.CDF = Mätning gjord 14 dagar efter inokulering, Pinus pinea inokulerad med F. circinatum, replikat nummer 4.
Alla in vitro-filer är namngivna enligt AAAA#* utom media blank som heter emabl#* där:
AAAA = Fusariumart (fcir=Fusarium circinatum, fgra=Fusarium graminearum, foxy=Fusarium oxysporum f.sp. pini, fbul=Fusarium bulbicola)
# = dagar sedan inokulering (7, 14 eller 21)
* = replikatnummer (1-3)
Exempel: fcir72.CDF = Fusarium circinatum, mätning gjord 7 dagar sedan inokulering, replikat nummer 2
Analys av flyktiga organiska ämnen för tidig detektion av Fusarium circinatum
Keywords: gas chromatography; gaskromatografi; plant health care; forest health; plant diseases; växtsjukdomar; biosecurity; biosäkerhet; plant health control; växtkontroll; mass spectrometry; solid phases; fusarium graminearum schwabe; fusarium bulbicola nirenberg & o'donnell; pinus radiata d. don; pinus sylvestris l.; fusarium circinatum nirenberg & o'donnell; fusarium oxysporum schltdl.; pinus pinea l.; fusarium; pinus; VOCs; VOCs; SPME; SPME; plant health; växthälsa; volatile organic compounds; volatila organiska ämnen; pathogens; patogener; Pine Pitch Canker; Tallens hartskräfta; bio security; biosäkerhet; disease detection; sjukdomsdetektion; Chemical Sciences; Kemi; Microbiology; Mikrobiologi; Engineering and Technology; Teknik; Forest Science; Skogsvetenskap